O Estado pós-neoliberal e os Programas de Transferência Condicionada de Renda no Brasil e na Argentina: ruptura ou continuidade? - Silva, Ivan Henrique de Mattos e (2018)
The period placed between the early 2000s and the mid 2010s set up new experiences on the horizon of Latin America that presented themselves as alternatives to the neoliberal hegemony that followed the processes of democratic reconstruction of the 1980s and 1990s. Respected the peculiarities and specificities of each case, those experiences were broadly defined as different expressions of a post neoliberal State. This work aims to analyze the patterns of rupture and continuity represented by the post neoliberal experiences of Brazil and Argentina, considering as the object what became the main state strategy to fight social asymmetries in the late twentieth century: the Conditioned Cash Transfer Programs, respectively the Programa Bolsa Família and the Asignación Universal por Hijo.